Morphological adjustments of mature Quercus ilex trees to elevated CO 2 - Hättenschwiler, S.; Miglietta, Franco; Raschi, Antonio; Körner, C. (Acta Oecologica, 1997)
It is still not known whether mature forest trees respond to increasing atmospheric CO 2 concen- trations in similar ways as seedlings do. Mature Mediterranean oaks (Qaercus ilex) growing in a CO 2 enriched atmosphere around natural CO 2 vents since the seedling stage showed a moderate, age- dependent increase in stem biomass production, but had significantly lower biomass of 6-year-old branches, decreased branching, and lower leaf area per unit branch biomass, compared to control trees at a nearby unenriched site. Our data indicate that trees in natural forest stands morphologically adjust to increasing CO 2 and reduce COz-induced initial growth stimulations. Allometric adjustments such as reduction in leaf area may be regarded as a "down-regulation" of canopy photosynthesis and may be an effective mechanism for saving water.
Keywords: allometric adjustments; biomass allocation; branch morphology; branching; leaf area; Mediterranean; natural co 2 springs; Quercus ilex

Morphological adjustments of mature Quercus ilex trees to elevated CO 2 (Acta Oecologica, 1997)
It is still not known whether mature forest trees respond to increasing atmospheric CO 2 concen- trations in similar ways as seedlings do. Mature Mediterranean oaks (Qaercus ilex) growing in a CO 2 enriched atmosphere around natural CO 2 vents since the seedling stage showed a moderate, age- dependent increase in stem biomass production, but had significantly lower biomass of 6-year-old branches, decreased branching, and lower leaf area per unit branch biomass, compared to control trees at a nearby unenriched site. Our data indicate that trees in natural forest stands morphologically adjust to increasing CO 2 and reduce COz-induced initial growth stimulations. Allometric adjustments such as reduction in leaf area may be regarded as a "down-regulation" of canopy photosynthesis and may be an effective mechanism for saving water.